Integrating Graphic-Enhanced, Interactive Triple R (GEI3R) Strategy to Foster Reading Comprehension in EFL - Aguete, Hannah Joyce N.; Abella, Angeline Norm Y.; Amancio, Rommel T.; Constantino, Almarie Jaen A.; Cruz, Mariecar A. De la; Lucas, Stella D.; Ribac, Fheiby A.; Fernando, Madeline T. (Journal of English Education, 2025)
This research employed the Graphic-Enhanced Interactive Triple R (GEI3R) Strategy as an intervention to enhance the reading comprehension of Grade IV pupils in their English classes. Total sampling was utilized in the schools where teaching interns conducted their practice teaching, as all the Grade IV pupils were observed to have poor reading comprehension. Specifically, it aimed to determine the level of pupils’ reading comprehension through a pretest and posttest and to identify improvements after the implementation of the GEI3R strategy. To achieve these objectives, the study employed a mixed-methods approach, collecting both quantitative and qualitative data using a researcher-developed pretest and posttest questionnaire, an interview guide, and an observation checklist, all of which were validated by experts. Descriptive statistics were applied to analyze the pretest and posttest results, while thematic analysis following the protocol of Braun and Clarke (2021) was used to analyze data from interviews. The study's findings confirmed the effectiveness of the GEI3R strategy, as evidenced by a significant increase in the posttest mean score (9.27) compared to the pretest mean score (2.27), with a significant mean difference of 7.00. Thematic analysis further revealed distinct themes that show how the strategy contributed to improvements in pupils' reading comprehension. This implies that the GEI3R intervention effectively enhanced the reading abilities of Grade IV pupils at Filipinas East, Santo Cristo, and Subec Elementary Schools, where the teaching interns conducted their practice teaching. Thus, the strategy is recommended for use in other schools, as it can be adapted to meet the diverse needs and contexts of learners within the Philippine basic education system.